Accidental hijab pin ingestion in Muslim women: an emerging endoscopic emergency?. (3rd January 2014) - Goh, Jason; Patel, Neeral; Boulton, Ralph
Abstract : Ingested foreign body is an infrequent indication for emergency endoscopy in the adult gastroenterology practice. We describe the clinical features and endoscopic management of the first four cases of accidental ingestion of hijab pins by Muslim women in our unit, all presenting within a 12-month period. The pins were all successfully retrieved without any complications. In this report, we review published guidelines and the current literature, as well as discussing the approach (conservative vs proactive endoscopic retrieval) and timing of endoscopic treatment. The Muslim community may need to be alerted to the potential health hazard of hijab pins.